Design and simulation of air-solar-finned reheating unit: An innovative design of a parabolic trough solar collector. Issue 1 (1st January 2020) - Nnamchi, S. N.; Nnamchi, O. A.; Onuorah, M. O.; Nkurunziza, K. O.; Ismael, S. A.
Abstract: Design and simulation of air-solar-finned reheating unit, an innovative design of a parabolic trough solar collector (PTSC) has been demonstrated in this work. Fundamentally, the design equations were formulated on the optical and thermal principles. The fundamental optical equations were transformed and equated with the original optical equations to realize the optical design functions. The design variables appear in the design function as the unknowns. The design functions were differentiated with respect to the design variables to form design simulatory matrices. Prior to the simulation, the design functions were made to approach zero by the introduction of convergent factors which guarantee the convergence of the simulatory matrices whose final output defines the design variables. The design was algorithmized with a flowchart to justify the design procedures. A slight obtuse-angled rim design was adopted in the design of the reheating unit (RU) which yielded optimum; rim angle of 94°, collector, optical and thermal efficiencies of 0.44, 0.72 and 0.31, respectively, and an optimum exit fluid temperature of 110 o C sequel to the simulation of the design equations. Besides, the apparent tradeoffs among the design variables were useful in making design decisions. Considering the pitfalls of the traditional acute-angled rim design (AARD), the present work is advocating for the adoption of slight obtuse-angled rim design (SOARD) technique which will shield the PTSCs from the misalignment issues and equally minimize the thermal losses prone to the acute-angled rim design technique. Also, premium on material selection is recommended for the effective operation of RU.